Multiple Renal Injuries Lead to Death in Postoperative Cardiac Surgery Even with Precocious Hemodiafiltrations - Mihaela Bizubac; Catalin Cirstoveanu; Cristina Filip; Alin Nicolescu; Ileana Barascu; Ruxandra Chirca; Alina Gaiduchevici; Doina Anca Plesca (Amaltea Medical Publishing House, 2021)
We present the case of a newborn diagnosed with perinatal asphyxia and secondary renal injuries, transposition of the great vessels and low systemic blood flow, treated with Prostaglandin, atrioseptostomy, followed by arterial switch surgery After the cardiac surgery the patient is oliguric and requires hemodiafiltration for 12 days, after which renal function is restored. In evolution, however, AVB (atrioventricular block) grade III occurs, followed by implanta-tion of permanent pacemaker, but another postoperative complication - chylothorax - leads to stopping electrical stimulation followed by severe cardiac dysfunction and, consequently, recurrent renal injury and anuria. Re-estab-lishing hemodiafiltration for another 7 days without recovery of renal function. Perinatal asphyxia, cardiac heart disease with low systemic blood flow, prostaglandin, atrioseptostomy, cardiac rhythms disturbances, chylothorax, sepsis, cardiac arrest are intriguing factors that bring renal injury. Their association greatly decreases the chance of survival even if the patient benefits from supportive treatment and early hemodiafiltration.